Strain Rate Sensitivity of a TRIP-Assisted Dual-Phase High-Entropy Alloy - Basu, Silva; Li, Zhiming; Pradeep, K. G.; Raabe, Dierk (Frontiers in Materials, 2018)
Dual-phase high-entropy alloys (DP-HEAs) with transformation induced plasticity (TRIP) have an excellent strength-ductility combination. To reveal their strain-rate sensitivity and hence further understand the corresponding deformation mechanisms, we investigated the tensile behavior and microstructural evolution of a typical TRIP-DP-HEA (Fe50Mn30Co10Cr10, at. %) under different strain rates (i.e., 5 × 10−3 s−1, 1 × 10−3 s−1, 5 × 10−4 s−1 and 1 × 10−4 s−1) at room temperature. The strain rate range was confined to this regime in order to apply the digital image correlation technique for probing the local strain evolution during tensile deformation at high resolution and to correlate it to the microstructure evolution. Grain size effects of the face-centered cubic (FCC) matrix and the volume fractions of the hexagonal-close packed (HCP) phase prior to deformation were also considered. The results show that within the explored strain rate regime the TRIP-DP-HEA has a fairly low strain rate sensitivity parameter within the range from 0.004 to 0.04, which is significantly lower than that of DP and TRIP steels. Samples with varying grain sizes (e.g., ~2.8 and 38 μm) and starting HCP phase fractions (e.g., ~25 and 72%) at different strain rates show similar deformation mechanisms, i.e., dislocation plasticity and strain-induced transformation from the FCC matrix to the HCP phase. The low strain rate sensitivity is attributed to the observed dominant displacive transformation mechanism. Also, the coarse-grained alloy samples with a very high starting HCP phase fraction (~72%) prior to deformation show very good ductility with a total elongation of ~60%, suggesting that both, the initial and the transformed HCP phase in the TRIP-DP-HEA are ductile and deform further via dislocation slip at the different strain rates which were probed.